Immuno-inflammatory tissue reaction to stainless-steel and titanium plates used for internal fixation of long bones - Voggenreiter, Gregor; Leiting, Stephan; Brauer, Holger; Leiting, Peter; Majetschak, Matthias; Bardenheuer, Mark Johannes; Obertacke, Udo (Biomaterials, 2002)
The immuno-inflammatory responses to stainless-steel (21 implants in 20 patients) and titanium plates (22 implants in 20 patients) used in the treatment of long bone fractures were studied immunohistochemically. All fractures healed without complications. In the soft tissue adjacent to the surface of the implants a dark discolouration of the tissue was visible in 18/21 stainless-steel and 20/22 titanium plates. Tissue specimens of all patients contained positive staining for macrophages (CD68-positive cells). Serial sections showed that the majority of cells were found to express the HLA-DR molecule indicating their activation. Many of the macrophages were surrounded by clusters of T-lymphocytes (CD3-positive cells). 17 out of 21 steel specimens and 15 out of 22 titanium specimens showed the infiltration of moderate amounts of cytotoxic T-lymphocytes (CD8-positive cells). Moderate amounts of B-lymphocytes (CD79α positive cells) were evident in four patients with steel and six patients with titanium implants. The results of the present study clearly demonstrate the presence of a marked inflammation and tissue reaction in the soft tissue covering stainless-steel and titanium plates used for internal fixation of fractures of long bones independently from the material used.
Gesehen am 05.05.2022